Educação sexual na adolescência: práticas intersetoriais entre a saúde e a educação - Vieira, Priscila Mugnai (2015)
Sexual and reproductive health is understood as one of the main dimensions of risk and vulnerability in adolescence and, therefore, is a priority for Public Policies that are aimed at this population. From this understanding, and also from the recognition of the potentials of intersectorality between Health and Education in regard of the care practices related to sexuality and reproductive health, this study focuses on the practices of sex education for adolescents, which are held in schools and health services. Main objective: To identify the perspectives and practices regarding the intersectoral work on Sex Education with teenagers from the perspective of Health and Education professionals in a large city in the state of São Paulo. Methodology: This study, which has a qualitative approach, has counted with the participation of 20 professionals, ten from the health sector related with the Family Health Strategy, and ten in the Education area linked to middle schools. In order to gather data, forms were used to characterize the professionals, the services and the Sex Education practices, and semi structured interview scripts were used as well. The data was analyzed with a Thematic Analysis, using previous researches and Public Policies as theoretical material. Results: In both sectors two models were identified related to the concept and practices of Sexual Education: the biological-centered model and the preventive and biopsychosocial model. In regard of the challenges of the practices, it was identified the need for training and support, and it was also identified resource scarcity and the need for organization, structuring and routine services. About the Public Policies related to Sex Education and to adolescence itself, in both sectors there was a perception that they bring contributions to the practices, although it was highlighted several weaknesses in the implementation of the proposals. About intersectoral Sex Education in the education sector, it was identified as potentialities: the exchange of knowledge, access to data, the acquisition of learning resources and increasing access of adolescents to health services. In the health sector, the identified potential of intersectoral were: co-responsibility, comprehensiveness and complementarity of care, and improved access of adolescents to health. Among the weaknesses on the intersectorality, it was found: Fragmentation and lack of co-responsibility between sectors; need for training. The results show a gap between what is granted by public documents and what is the reality of Sex Education, thus the practices remain less than what is expected in both sectors. Specifically about intersectorality, there are evidences that the health sector presented itself as more appropriate and able to achieve integrated practices, whereas it is in the education sector that these practices have been performed predominantly. It is discussed that the practices in both sectors require higher qualifications regarding the contents being addressed, the methodologies, training, among others aspects. It is considered the possibility that intersectoral practices on sexual education, although made effective in schools, still need investment and increased mobilization of the professionals of both sectors. However, it is understood that the health sector can contribute with more features for the initial implementation.